Investigating inhibition of return with converging interdisciplinary methods - Eng, Vivian Jin Lin (2020)
This dissertation investigates inhibition of return (IOR) as two forms of inhibitory cueing effects operating on spatially uninformative visual stimuli (i.e., cues): an output form of IOR that is generated when saccades are permitted, and an input form of IOR that arises when saccades are not allowed. Using paradigms adapted from Posner’s (1980) spatial cueing task, our first set of experiments in Chapter 2 attempts to dissociate the two forms of IOR by incorporating an incompatible response paradigm that requires either saccadic or manual keypress responses to targets. This design allowed us to examine separately the input form of IOR at the stimulus level versus the output form that is response related. The event-related potential (ERP) study in Chapter 3 builds upon the previous paradigm but uses saccades to cues to activate the oculomotor system. The activation of the oculomotor system allowed us to probe the neural mechanisms underlying the inhibitory cueing effects that are usually exhibited and studied in terms of behavioural response times. By manipulating stimulus-response compatibility in combination with activation or suppression of the oculomotor system in Chapters 2 and 3, we showed that the input form of IOR can be observed behaviourally when the oculomotor system is supressed. However, since we are ultimately looking for evidence of output-based IOR, which we have not been able to show with the anti-localisation paradigm, we decided that a change in direction was necessary. Chapters 4 and 5 present a shift in focus towards investigating modulations of behavioural cueing effects associated with the inclusion of non-targets (i.e., distractors) in a discrimination-localisation task. Our time-course study laid out the development of IOR in a distractor paradigm, and the results indicate that when distractors are present, oculomotor IOR starts early and slowly decays, whereas sensory-based IOR emerges later but decays relatively faster. The visually balanced ERP experiment in Chapter 6 allowed us to study the N2pc component as a neurophysiological marker of the output form of IOR while the oculomotor system is activated. We provide convincing evidence for behavioural IOR despite the presence of distractors, although ERP results are less clear cut. This dissertation provides converging evidence in support of an input based sensory/attentional IOR that is distinct from output based oculomotor IOR.